2002
DOI: 10.1046/j.1461-9563.2002.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating disruption of the pine sawfly Neodiprion sertifer (Hymenoptera: Diprionidae) in isolated pine stands

Abstract: 1 Previous applications of the mating disruption technique to Neodiprion sertifer resulted in decreased numbers of males caught in the treated area but no effect on sex ratio or overall population density. 2 The present study assessed the efficacy of mating disruption against N. sertifer outbreaks in pine stands surrounded by agricultural areas or pasture, and therefore isolated from other infested areas. 3 Pine stands were treated by placing dispensers with an erythro-mixture of the acetate ester of 3,7-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…The present study gives clear evidence that this hypothesis was not correct. In a recent publication Martini et al. (2002) showed that mating disruption of N. sertifer can both alter the sex ratio and reduce the populations in small isolated pine stands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study gives clear evidence that this hypothesis was not correct. In a recent publication Martini et al. (2002) showed that mating disruption of N. sertifer can both alter the sex ratio and reduce the populations in small isolated pine stands.…”
Section: Resultsmentioning
confidence: 99%
“…The present study gives clear evidence that this hypothesis was not correct. In a recent publication Martini et al (2002) showed that mating disruption of N. sertifer can both alter the sex ratio and reduce the populations in small isolated pine stands. Thus, the assumption that it is the movement of mated females from surrounding areas that obstructs the effect of mating disruption in non-isolated areas still remains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neodiprion abietis females (Knerer and Atwood 1973), as well as females from other diprionid species (reviewed in Martini et al 2002), have been reported to have very limited dispersal activity. Nevertheless, during the early stages of outbreaks, adult immigration was clearly associated with population increase because values of recruitment reached 500 eggs per adult even though N. abietis females rarely lay more than 75 eggs (Moreau and Quiring 2011).…”
Section: Factors Associated With Population Increase and Declinementioning
confidence: 99%
“…Females of several pine sawfly species emit sex pheromones that attract males for mating. An alternative method to control and reduce the population is to use the insects own sex pheromone for monitoring, mass capture or mating disruption (Östrand et al, 1999;Rieske et al, 2001;Martini et al, 2002). The pheromone is stored as an alcohol precursor in the female body, which is esterified at the moment of release from the insect (Jewett et al, 1976;Anderbrant et al, 2005).…”
Section: Introductionmentioning
confidence: 99%